Liberal White Supremacy : How Progressives Silence Racial and Class Oppression. - Beeman, Angie (Sociology of Race and Ethnicity Ser., 2022)
"In this book, the author argues that white supremacy is maintained, not only by right-wing conservatives or stereotypically uneducated and/or working class racial bigots, but by progressives who operate from a liberal ideology of color-blindness, racism-evasiveness, and class elitism. By distinguishing between liberal and radical approaches to racism, class oppression, capitalism, and social movement tactics, the author shows how progressives continue to be limited by liberal ideology and perpetuate rather than dismantle white supremacy, all while claiming to be anti-racist. She conceptualizes this process as "liberal white supremacy," the tendency for liberal European Americans to constantly place themselves in the superior moral position in a way that reinforces social injustice. While there is a perception of a fragmented left, few have explicitly outlined what this fragmentation involves. This distinction provides insight on divisions among progressives at both the local level, in community organizations, and the national level in the Democratic Party. The author advances what she calls action-oriented and racism-centered intersectional approaches as alternatives to progressive organizational strategies that either downplay racism in favor of a class-centered approach or take a talk-centered approach to racism without developing explicit actions to challenge it"--